Antioxidant Activity Study And Α-glucosidase Inhibitor Phenolic Leaf Extract Bungur (Lagerstroemia speciosa) From Meru National Park Betiri - Jainur Rochman; Tri Agus Siswoyo; A.A. Istri Ratnadewi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
Study activities phenolic extract of bungur leaf as an antioxidant and inhibitor for the enzyme α-glucosidase was performed by spectrophotometric method. The extraction was carried out by three solvents with different polarity level in order to get three types of extracts namely hexane extract Bungur (HB), ethyl acetate extract Bungur (EAB), and the methanol extract Bungur (MB). The units, used in the analysis, is the total phenolic that standardized in gallic acid. The antioxidant activity of phenolic extracts Bungur leaf can be seen from its ability to reduce free radicals through the damping test DPPH radical, superoxide anion, and hydroxyl. Potential extract phenolic leaf Bungur as an inhibitor of α-glucosidase were analyzed by inhibition of α-glucosidase, but in this study also tested the inhibition of the enzyme α-amylase because both of these enzymes worked on the digestive system and hydrolyze carbohydrates. The results generally showed that the methanol extract of leaves Bungur potential as antioxidants that compared with standard vitamin C. In addition, it had as well as potential for inhibitors of α-glucosidase and α-amylase that compared akarbosa standard, which is expected to be a natural antidiabetic agent.Keywords: phenolic, bungur, antioxidant, inhibitor, α-amilase, α-glukosidase